A numerical study on capillary-evaporation behavior of porous wick in electronic cigarettes - Yihan Gao (Nature Portfolio, 2021)
Abstract A mathematical model based on heat and mass transfer processes in the porous wick of electronic cigarettes was established to describe the atomization of e-liquids according to max liquid temperature, vaporization rate and thermal efficiency in a single puff. Dominant capillary-evaporation effects were defined in the model to account for the effects of electrical power, e-liquid composition and porosity of the wick material on atomization and energy transmission processes. Liquid temperature, vaporization rate, and thermal efficiency were predicted using the mathematical model in 64 groups, varying with electrical power, e-liquid composition and wick porosity. Experimental studies were carried out using a scaled-model test bench to validate the model’s prediction. A higher PG/VG ratio in the e-liquid promoted energy transfer for vaporization, and the e-liquid temperature was comparatively reduced at a relatively high power, which was helpful to avoid atomizer overheating. Compared with the other factors, wick porosity affected the thermal efficiency more significantly. The vaporization rate increased with a higher wick porosity in a certain range. The modelling results suggested that a greater wick porosity and a higher PG ratio in e-liquids helped to improve the overall thermal efficiency.